2022
DOI: 10.3389/fonc.2022.734948
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Pretreatment Neutrophil-to-Lymphocyte Ratio, Platelet−to−Lymphocyte Ratio, or Monocyte-to-Lymphocyte Ratio in Endometrial Neoplasms: A Systematic Review and Meta−analysis

Abstract: AimNeutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), or monocyte–lymphocyte ratio (MLR) has been shown to be related to the poor prognosis of cervical cancer, ovarian cancer, breast cancer, and other malignant tumors, but their role in predicting the prognosis of endometrial cancer is still controversial. Therefore, we conducted this meta-analysis to evaluate the effectiveness of NLR more accurately, PLR, or MLR in predicting the prognosis of endometrial cancer (EC).MethodsThis review systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…There are several limitations in the current study. First, several peripheral blood count-based biomarkers have been previously investigated in various cancers, before and after the advent of ICIs, such as the neutrophil-to-lymphocyte ratio [ 52 , 53 , 54 , 55 , 56 ], lymphocyte-to-monocyte ratio [ 52 , 55 , 57 ], and platelet-to-lymphocyte ratio [ 52 , 54 , 58 , 59 , 60 ]. The current study chose to investigate NER (instead of other indices) based on our clinical observation of eosinophil count elevation and the established prognostic role of neutrophilia in mRCC in the IMDC model [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations in the current study. First, several peripheral blood count-based biomarkers have been previously investigated in various cancers, before and after the advent of ICIs, such as the neutrophil-to-lymphocyte ratio [ 52 , 53 , 54 , 55 , 56 ], lymphocyte-to-monocyte ratio [ 52 , 55 , 57 ], and platelet-to-lymphocyte ratio [ 52 , 54 , 58 , 59 , 60 ]. The current study chose to investigate NER (instead of other indices) based on our clinical observation of eosinophil count elevation and the established prognostic role of neutrophilia in mRCC in the IMDC model [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mean corpuscular volume, mean platelet volume, neutrophil percentage, lymphocyte percentage, and neutrophil/lymphocyte ratios in whole blood were significantly correlated with frozen results. As there are many examples in the literature [15][16][17][18][19], these parameters, which play a role in the inflammatory process, had data that could provide clues in the differentiation of benignborderline-malignant during surgery. We found that blood lymphocyte ratio, Ca-125, and neutrophil/lymphocyte ratio values have the most significant findings regarding the parameters that are the most predictive feature of the malignancy indicator.…”
Section: Discussionmentioning
confidence: 99%
“…The subtypes of WBCs may undergo relative changes under stress or systemic inflammation; thus, the derived ratios may also reflect the patients’ immune-inflammatory status and indicate their outcomes [ 9 , 10 ]. NLR, MLR, and PLR have been widely investigated as new inflammatory markers in many inflammatory, cardiovascular, and malignant diseases [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and have been thought to be simple, inexpensive, and easily assessed predictors.…”
Section: Introductionmentioning
confidence: 99%